Implementing the Ummi Method for Qur'an Tahsin to Improve Qur'an Teaching Skills of Teachers - Wajdi, Muh Barid Nizarudin; Mukhlisin, Mukhlisin; Sari, Rahmat Julia Rafika; Kurniawan , Ari; M, Mimin Nuraini (STAI Miftahul ULa Nganjuk, 2023)
This study aims to implement the Ummi Method in Qur'anic reading (Tahsin) to enhance the teaching skills of Al-Qur'an teachers. The research employs the Action-Based Collaborative Development (ABCD) approach, which involves four stages: needs analysis, model development, implementation, and evaluation. The results of the study indicate that the Ummi Method significantly improves teachers' ability to manage classrooms effectively, as well as their skills in teaching Qur'anic reading with correct Tajweed and Makharij. Furthermore, students demonstrated improved fluency in reading the Qur'an and a better understanding of Tajweed rules. However, challenges such as limited resources, time constraints, and an insufficient number of teachers were identified as factors hindering the optimal implementation of the method. The study concludes that continuous training for teachers, improved facilities, and better time management are necessary for maximizing the effectiveness of the Ummi Method in Qur'anic education